Social Networking Sites usage and Academic Deviance among Girl students of Higher Secondary Schools in Kerala - Chandran, Anjana V.R; Raj. T., Sundara (JOURNAL OF INDIAN EDUCATION, 2020)
Social networking sites are web based services that create virtual communities in which people connect and interact with friends, family and acquaintances; it also offers platform for sharing multimedia objects. Younger generations, especially students are the major and frequent users of social networking sites. Shifting trend and behaviour is seen among students with the advent of new multimedia technology and they are more dependent on technology so that it is imperative to find out its effects on the academic activities and whether it is leading to any deviance on their part. The present study investigates the extent of academic deviance and its relation with usage of social networking sites among higher secondary school female students. Data for the study was collected from 160 higher secondary school female students using social media with the help of the academic deviance scale. Percentage, ANOVA, correlation and regression were used to test the significance of difference. Study reveals that there exists significant difference in the academic deviancy score among the various levels of social media users.